LANGUAGE DEVELOPMENT IN EARLY CHILDHOOD - Srisofian Sianturi; Ernawati Tampubolon (Universitas PGRI Palembang, 2025)
This study investigates the early language development of children aged one to two years through the lens of Jean Piaget’s cognitive development theory. Utilizing a descriptive qualitative approach, the research involved longitudinal observations of three toddlers Cinta, Adriel, and Arvin over a six-month period, focusing on their verbal output, contextualized speech, and interactional behaviors. The analysis revealed that the children exhibited both expressive and receptive language competencies, manifesting in the use of single-word utterances, two-word combinations, and telegraphic speech structures. Key determinants influencing the trajectory and nature of their language acquisition included familial communication, the presence and responsiveness of caregivers, and the richness of the home linguistic environment. These findings align with Piaget’s assertion that language development is intrinsically linked to cognitive maturation, wherein children begin to utilize verbal symbols to represent people, objects, actions, and affective states. The study highlights the foundational importance of early social interaction and emotional bonding in facilitating linguistic growth during the sensorimotor and initial preoperational phases of development.